(3GdgOGjI Edi HdhZ GdfgGjI aj Yde eYGfi GdbQBfs - (3nepqcj Hf CHj WGdH nMoqehT Hf eMeO Hf eNJGQ GdCfOdSj GdbjSj, CHh eMeO,J (B437 (3g` s ((3eMeO Hf Ydi Hf eMeO GdOQYi GddLdGLdi s)
(3ChdgG (B:s
(3JaSjQ ShQI GdeDef (B( (3ZGaQ (B) s
(3BNQgG (B:s
(3jfJgi HBNQ GdbQBf GdcQje Hbhdg (B: - (3hef UfYJg GdMcje dCfg jMce GdfGS HQOge Edi GdMb bhdge (B: (3Mceg UOb Gddg GdYXje s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs